State of the art: gene therapy of haemophilia. (July 2016) - Spencer, H. T.; Riley, B. E.; Doering, C. B.
Abstract : Clinical gene therapy has been practiced for more than a quarter century and the first products are finally gaining regulatory/marketing approval. As of 2016, there have been 11 haemophilia gene therapy clinical trials of which six are currently open. Each of the ongoing phase 1/2 trials is testing a variation of a liver‐directed adeno‐associated viral (AAV) vector encoding either factor VIII (FVIII) or factor IX (FIX)1 . As summarized herein, the clinical results to date have been mixed with some perceived success and a clear recognition of the immune response to AAV as an obstacle to therapeutic success. We also attempt to highlight promising late‐stage preclinical activities for AAV‐FVIII where, due to inherent challenges with manufacture, delivery and transgene product biosynthesis, more technological development has been necessary to achieve results comparable to what has been observed previously for AAV‐FIX. Finally, we describe the development of a stem cell‐based lentiviral vector gene therapy product that has the potential to provide lifelong production of FVIII and provide a functional 'cure' for haemophilia A. Integral to this program has been the incorporation of a blood cell‐specific gene expression element driving the production of a bioengineered FVIII designed for optimal efficiency. As clearly outlined herein, haemophilia remains at the forefront of the rapidly advancing clinical gene therapy field where there exists a shared expectation that transformational advances are on the horizon.